Batch Adsorption of Pb(II) Batch Using Humic Acid from Goat Dung - Malikhatul Hidayah; Kustomo Kustomo; Anfi'na Ilma Yunita (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2022)
This research focuses on the batch adsorption process, then looks for kinetic models and Freundlich model adsorption isotherms. In the process of adsorbing the heavy metal Pb, humic acid from goat dung has the potential to be employed as a promising adsorbent since it offers benefits, including being economical, being able to work accurately, quickly, sensitively, selectively, and helping to maintain public health. Parameters for testing humic acid from goat dung as an adsorbent for heavy metal Pb were determined by optimizing pH test variations, contact time, and concentration of Pb solution. Humic acid from goat manure could work optimally to absorb heavy metal Pb at pH 5, contact time 30 minutes, and metal concentration Pb 20 ppm with an adsorption capacity of 19.784 mg/g. Data modeling revealed that the adsorption process followed a pseudo-second-order kinetics model with the acquisition value of R² = 0.9595 and the Freundlich isotherm with the acquisition value of R² = 0.9166.